Decision-making for PCV in adults. Issue 3 (4th March 2019) - McLaughlin, John M.; Swerdlow, David L.; Isturiz, Raul E.; Jodar, Luis
ABSTRACT: Thirteen-valent pneumococcal conjugate vaccine (PCV13) was licensed in adults to address the unmet medical need of vaccine-type community acquired pneumonia (CAP) and the limitations of previous plain-polysaccharide vaccines. Since then, some have questioned the utility of adult PCV13 use, arguing that: i) high PCV13 uptake in young children would provide indirect effects that, by themselves, would sufficiently protect unvaccinated adults and ii) no data describing the real-world effectiveness of PCV13 use in adults, especially with immunocompromising conditions, exist. Even in countries like the United States where PCV13 has been routinely recommended for all adults aged ≥ 65 years, the recommendation is contingent on a re-evaluation to determine if continued use is needed in the context of a mature PCV13 pediatric immunization program. Emerging evidence, however, suggests that i) a meaningful burden of PCV13-type pneumococcal pneumonia still persists in adults at increased risk for pneumococcal disease, despite indirect effects from long-standing pediatric PCV13 use, ii) adult PCV13 use is effective and has reduced pneumococcal CAP, even in the elderly and those with chronic medical or immunocompromising conditions – and disease could come back if PCV13 were removed, and iii) ethical and pragmatic vaccine policy considerations support continued adult PCV13 use in countries that have already introduced the vaccine (eg, disparities in adult PCV13 uptake, confusion stemming from removing a previously-recommended vaccine for a non-safety-related concern, and the reality that next-generation PCVs are only a few years away). Together, these findings suggest that continued PCV13 vaccination in adults is needed to control vaccine-type CAP.